Oligomycin, an F1FO-ATPase Inhibitor, Protects Against Ischemic Acute Kidney Injury in Male but Not in Female Rats - Ryosuke Tanaka; Junji Takayama; Masanori Takaoka; Yohko Sugino; Mamoru Ohkita; Yasuo Matsumura (Elsevier, 2013)
We investigated the effects of oligomycin, an F1FO-ATPase inhibitor, on ischemic acute kidney injury in male and female rats. Ischemic acute kidney injury was induced by clamping the left renal artery and vein for 45 or 60 min followed by reperfusion, 2 weeks after contralateral nephrectomy. Renal dysfunction and histological renal damage were observed 1 day after reperfusion in both male and female rats, although these renal injuries were more marked in male rats than in female rats. Intravenous bolus injection of oligomycin (0.5 mg/kg) 5 min before ischemia markedly attenuated the ischemia/reperfusion-induced renal injury in male rats. However, oligomycin did not show the protective effect in female rats subjected to ischemia/reperfusion-induced renal injury. Pre-ischemic treatment with oligomycin suppressed partly but significantly ischemia-induced renal ATP depletion only in male rats. These results indicate that oligomycin prevents the onset of ischemic acute kidney injury in male but not in female rats, and the effect is accompanied by suppression of the ATP depletion only in the male rat kidney during ischemia, thereby suggesting that the ATP hydrolysis pathway by mitochondrial F1FO-ATPase induces a sex difference in ischemic acute kidney injury. Keywords:: ischemic acute kidney injury, sex difference, ATP depletion, F1FO-ATPase, oligomycin